Environmental policy is social policy - social policy is environmental policy : toward sustainability policy - Wallimann, Isidor (Springer New York, 2013)
If sustainability is our goal, social and environmental policy must be treated as one and the same field. Examples from Agriculture, Nutrition, Forestry, Urban Planning, Care Work, Tourism, and University Management show that such a paradigm shift is indicated, important, and timely. They also show that Environmental or Social Impact Assessments are no longer adequate. The new paradigm synthetically combines environmental and social policy. Not to do so leads to policy inefficiency and perverse effects. One policy domain may counteract or outright "sabotage" the other. To synthetically combine environmental and social policy calls for a trans-disciplinary perspective to include both policy fields and academic disciplines. This is well illustrated by the contributors in this book who represent numerous academic disciplines. They help professionals and students appreciate the centrality of trans-disciplinary thought and practice in working toward sustainability.